Evaluate the Effect of Traditional Approach (Basti Chikitsa and Ayurveda Formulations) in the Management of Benign Prostate Hyperplasia (BPH) (AYUSHDHARA, 2024)
Benign Prostate Hyperplasia (BPH) is defined as the proliferation of prostatic stromal cells, which results in an enlarged Prostate gland. As result the prostatic urethra is compressed, which restricts the flow of urine from the bladder. BPH is a burning senile problem of elderly men, associated with lower urinary tract symptoms such as frequent urination, urgency, nocturia, intermittent force of stream, and the sensation of incomplete bladder emptying, usually seen in after 5th decade. In Ayurveda, Vatashtheela disease closely resembles with BPH of modern medicine in its sign and symptoms. It is manifested due to improper function of Apana Vayu along with the vitiation of Kapha and Pitta dosha. In this case study, a patient diagnosed with Benign Prostatic Hyperplasia was treated with a Dashmoola Kwath Niruha Basti and Bala oil Anuvasana Basti (3:1 ratio in plan) for 30 days and followed by oral administration of Chandraprabha vati, Varunadi kashayam, Haritaki churna, Amla churna, Haridra churna and Amrutadi guggulu for 3month in follow-up period. After completion of the treatment, changes in the subjective criteria (by IPSS) and changes in the objective criteria (by USG) were recorded. Finally, study concluded that given treatment is found to be highly effective in the management of Benign Prostate Hyperplasia (BPH).